Studies of the Listeria species in some meat and meat products consumed in Elazig city - Güven, A; Patir, B (Scientific Technical Research Council Turkey, 1998)
In this study, the presence of Listeria species in various meat products obtained from different meat markets in Elazig city was studied. For this purpose 100 minced meat, 80 poultry meat, 80 sausage and 70 chopped meat samples were analysed. The samples were incubated at 30 degrees C for 48 hours and 7 days respectively using two different enrichment methods. These incubations were performed for enrichment of potantial Listeria species in the samples which were inoculated onto Listeria Selective Agar Base (LSA), McBride Agar (MBA) and Modified McBride Agar (MMBA) media. In addition the rest of the same samples were enriched at 30 degrees C for 48 hours and 7 days after being kept at -8+/-1 degrees C for 10 days. At the end of initial 48 hours enrichment Listeria species were present in 35 % minced meat samples and the percentage of minced meat samples with L. monocytogenes, with L. innocua and with Listeria species were 13, 26 and 4 % recpectively. After 48 hours enrichment of the same samples that were kept previously at -8+/-1 degrees C for 10 days L. monocytogenes were present in 10 whilst L. innocua occurred in 19 of the samples recpectively. In poultry meat after the 48 hours enrichment L. monocytogenes, L. innocua and Listeria species were present 38.8, 50, 60 % of the samples recpectively. After 48 hours enrichment of the same samples that were kept previously at -8+/-1 degrees C for 10 days L. monocytogenes were present in 15 whilst L. innocua occurred in 33.8 % of the samples recpectively. In the sausage samples after 48 hours enrichment L. monocytogenes and L. innocua were determined in 7.5, 11.4 % of the samples recpectively. After 10 days examination L. monocytogenes were present in 15 whilst L. innocua occurred in 10 % of the samples recpectively. In chopped meat samples after 48 hours enrichment L. monocytogenes and L. innocua were noticed in 11.4 and 18.6 % of samples. After 48 hours enrichment of the same samples that were kept previously at -8+/-1C for 10 days L. monocytogenes were present in 10 whilst L. innocua occurred in 12.9 % of the samples recpectively. In conclusion LSA media seems to be suprerior to MBA and MMBA media for the isolation of Listeria species from meat samples. The results obtained from MBA and MMBA were similar. The rate of Listeria species contamination determined after 48 hours enrichment was higher than that obtained from 7 days enrichment. Most of the Listeria species were still viable after the samples being kept at -8+/-1 degrees C for 10 days. L. monocytogenes contamination was higher particularly in minced meat and poultry meat samples, that sould be considered as a serious threat to public health.
Keywords: Listeria spp.; minced meat; sausage; chopped meat; chicken meat